Lipomatous basal cell adenoma (Basal cell lipoadenoma) – Report of the first two cases - Petersson, Fredrik; Agaimy, Abbas (Annals of Diagnostic Pathology, 2020)
We present, to the best of our knowledge, the first two cases (60 year old female and 71 year old male) of basal cell adenoma with significant adipocytic components and suggest the term “lipomatous basal cell adenoma” for these lesions. Both tumors presented as slow growing nodules in the parotid gland. The two cases represent different points on a histopathological spectrum with one case being extremely well differentiated with distinct spiradenoma-like histological features; distinct bilayering, duct formation with secretory material and very low proliferative activity and the other case displaying more primitive cytological features composed of a predominant uniform, (p63-positive; CK 7-negative) basaloid, abluminal cell type, high proliferative activity and only scattered true ducts composed of (CK7-positive, p63-negative) luminal cells.
CRIS-Team Scopus Importer:2019-12-31
Keywords: Basal cell adenoma; Lipoma; Lipomatous; Metaplasia; Salivary gland